A simplified approach to estimate settlements of earth embankments on piled foundations: the role of pile shaft roughness. Issue 1 (2nd January 2023) - Flessati, Luca; di Prisco, Claudio; Corigliano, Matteo; Mangraviti, Viviana
Abstract: The use of piles as settlement reducers in the design of artificial embankments on soft soil strata is nowadays very common. The design methods employed in the current engineering practice are based on simplified approaches not allowing the assessment of average and differential settlements at the top of the embankment. In this paper, a model to estimate both differential and average displacements at the top of the embankment is introduced. This, based on the choice of substructuring the spatial domain and employing a suitably conceived upscaling procedure, is an extension to the case of rough pile shafts of a model originally conceived by the authors for smooth piles. To conceive and calibrate the model, the authors performed a series of numerical simulations mainly aimed at highlighting the mechanical processes taking place at the pile shaft. From a practical point of view, this model can fruitfully be employed in displacement based design approaches and to optimize pile diameter and spacing.